2023
DOI: 10.1108/sef-11-2022-0518
|View full text |Cite
|
Sign up to set email alerts
|

Time and frequency uncertainty spillover among macro uncertainty, financial stress and asset markets

Abstract: Purpose This study aims to examine the uncertainty spillover among eight important asset classes (cryptocurrencies, US stocks, US bonds, US dollar, agriculture, metal, oil and gold) using weekly data from 2014 to 2020. This study also examines the US macro uncertainty and US financial stress spillover on these assets. Design/methodology/approach The authors use time–frequency connectedness method to study the uncertainty spillover among the asset classes. Findings This study’s findings revealed that the un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Adani is the third conglomerate to have crossed the US $200 billion market capitalization mark (Sonavane, 2022). This reflects the quantum of impact it may have on investors worldwide and may have a profound impact on the psychology of investors in terms of trust in the entire investment industry.…”
Section: Adani Group and Hindenburg Research Llcmentioning
confidence: 99%
See 1 more Smart Citation
“…Adani is the third conglomerate to have crossed the US $200 billion market capitalization mark (Sonavane, 2022). This reflects the quantum of impact it may have on investors worldwide and may have a profound impact on the psychology of investors in terms of trust in the entire investment industry.…”
Section: Adani Group and Hindenburg Research Llcmentioning
confidence: 99%
“…One of the recent events, that is, the Russia‐Ukraine war, majorly impacted the most important trade partners of Russia, that is, Germany, Austria, and Italy (Aliu et al., 2023). The interconnectedness of financial stress and uncertainty can disturb the market sentiments, impacting the overall trust of investors in the stock market system (Sawarn & Dash, 2023). As one of the earliest studies, Fama et al.…”
Section: Background Literaturementioning
confidence: 99%
“…In other words, the higher the uncertainty level, the lower the level of connectedness among currencies Tong et al (2022) quantified the impact of attention from the search engine (Google Trends) and social media attention (Twitter) and documented bi-directional causality between these attentions and cryptocurrencies. Sawarn and Dash (2023), using a time frequency-based connectedness, concluded that US financial stress transmits uncertainty to cryptocurrencies on a net basis. Long et al (2022) investigated the crosssectional impact of geopolitical risk on the returns of 2000 cryptocurrencies, establishing that cryptos with higher geopolitical betas tend to underperform those with the lowest betas.…”
Section: Introductionmentioning
confidence: 99%
“…Our study clarifies various concerns that have been discussed for many years but have yet to be settled. Some scholars put special emphasis on the question of whether the recent increase in the volatility of real exchange rates is related to the recent increase in the volatility of oil prices (Chortane and Pandey, 2022), while others have pointed out that it is important to consider whether or not the fluctuation of the dollar’s value relative to other major currencies correlates with fluctuations in the dollar’s commodity prices (Kisswani et al , 2019; Sawarn and Dash, 2023).…”
Section: Introductionmentioning
confidence: 99%